Metal-saving technology for manufacturing thick-walled pipes from continuously cast billets on a pilgrim mill - Balakin , V.F.; Stasevsky , S.L.; Uhriumov , Yu.D.; Balakhanova , T.V.; Uhriumov , D.Yu. (Theory and Practice of Metallurgy, 2023)
The methods of reducing metal waste during the production of especially thick-walled pipes with D/S<6 h on a 5-12″ polygrim unit at the INTERPIPE NTRP are examined. from non-recast billets. Increases the depletion coefficient of the metal during the rolling of pipes on a plating mill due to the peculiarities of the technology, in order to increase the shape of the front (seed) and rear ends of the pipes, which create the saws makeup head. At this rate of metal, the hour of rolling pipes on a unit with a rolling mill is 50-100 kg per ton of pipes, lower on other units (with automatic, non-interruptible mills). Based on theoretical analysis and experimental data from the current industrial production, it was determined that the method of hot rolling of liners can be used to remove D/S<6 pipes with a clear structure from the metal of finished pipes, including and at the rear ends, similar to the polygrimic head. The results of the investigation can be used for rolling thick-walled pipes with D/S<6 of a wide range of sizes and grades on printing units with minimal waste of metal into the seed and the printing head.